La justice dans Les Criminels de Bruckner - Catherine Ailloud-Nicolas (Criminocorpus)
Bruckner’s play, The Criminals, appears as an interlacing of speech on the justice: words of characters which everything pushes towards the crime, conversations about laws which make references to Rousseau, Pascal and Freud, spectacle of four trials which take place mercilessly until the verdict. In the particular context of the Weimar Republic, the justice becomes the symptom of a faintness which gangrenes the whole society. However, is the play, for all that, a didactic one ? Is the positioning of the playwright political? To stage the justice, is it necessarily to criticize it?